Essays on Islamic piety and mysticism - Meier, Fritz 1912- (Islamic history and civilization : studies and texts, 1999)
Fritz Meier is one of the most outstanding Orientalists of this century. This text provides a translation of 15 of Fritz Meier's seminal articles. Articles deal with the history of Sufism, Sufi morals and practices, and the historical development of the master-disciple relationship.